Enhanching Lifelong Learning Through Multimedia and New Technology - Monica Troka (CV TOPAZART, 2022)
Applying new technologies in learning has made constant professional development even more critical for teachers. As a result, they must be able to keep up with technological developments in the school. Their professional development includes constantly updating their skills and knowledge of how they can meet the needs of their students or solve problems that result from the use of computer technology in the learning. Online learning apps open up new opportunities for professional development by staying up to date with the skills and topics required for professional work. This paper aims to contribute to assessing the impact of online learning applications on teacher professional development by presenting specific case studies and proposing new technological tools to collect useful income-supporting quantitative metrics.